SURFACE LOADING RATE IN FACULTATIVE STABILIZATION PONDS FROM NICARAGUA (Nexo Revista Científica, 2017)
Stabilization ponds are a viable alternative for municipal wastewater treatment, as it is a natural, low-cost operation and maintenance process. In Nicaragua there are 17 treatment plants for stabilization ponds, of which 13 are given treatment to wastewater from the municipalities of Nicaragua Pacific. One of the most used models for the design of stabilization ponds is the Surface Loading Rate, which contains several calculation methods proposed by different authors. However, in the Nicaraguan legislation there are insufficient criteria to define the method to be used, so each designer is free to use as he pleases. It is for this reason that the present investigation defined the method of calculation of Surface Loading Rate that best adapts to the treatment plants under study.